Fatal native aortic valve fungal endocarditis caused by Aspergillus flavus: A case report - Abdulrahman F. Al-Mashdali (17148316) (2021)
Fungal endocarditis is a rare condition, specifically in immunocompetent patients. Aspergillus species are the etiology in less than 30% of the cases. Moreover, Aspergillus flavus endocarditis is extremely rare and reported in only 7% of the total Aspergillus endocarditis cases. The most common predisposing factors are immunocompromised state, prosthetic valve, and previous cardiac surgery. In most cases, the diagnosis is delayed and occasionally missed. Prompt medical management combined with early surgical intervention is recommended once the diagnosis is established since the mortality rate is nearly 100% without surgical intervention. We report a rare and fatal case of native aortic valve endocarditis in a 49 years old diabetic patient who presented with fever and abdominal pain, complicated by multiple septic embolizations (splenic infarction, cerebral emboli, and limbs ischemia), and in which A. flavus was confirmed post mortem. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2021.e01310